A novel haemostatic agent based on self-assembling peptides in the setting of nasal endoscopic surgery, a case series. (2017) - Lee, M.F.; Ma, Z.; Ananda, A.
Highlights: A novel purely synthetic topical haemostatic agent is proposed for use in endonasal surgery. The mechanism is based on the self-assembling tendency of four repeating peptide sequences. The haemostatic agent was used in 60 patients undergoing endonasal powered turbinoplasty. Routine post-operative followup at 4 weeks has shown no re-bleeding or adhesion formation in all 60 patients. Pending further research, the agent shows promise in endonasal surgery as both a haemostatic and anti-adhesive adjunct. Abstract: Introduction: Recently, a novel purely synthetic topical haemostatic agent (PuraStat ® ) has been proposed in surgery based on the self-assembling tendency of some repeating peptide sequences. This transparent, ready to use hydrogel appears suitable for use in FEES with low rates of post-operative re-bleeding and adhesion formation. A first series of 60 patients experiencing endonasal powered turbinoplasty across various hospitals in Sydney using PuraStat ® was observed for postoperative re-bleeding and adhesion formation. Discussion: In all 60 patients, no post-operative re-bleeding was observed, while healing went well in absence of adhesion formation. Effective haemostasis with PuraStat ® is well documented in other surgical fields, but its use in FEES and adhesion prevention is relatively novel. Conclusion: Synthetic self-assembling peptides appear to be indicated in this area. Further studies are needed to confirm their potential for adhesion prevention.